Gender Stereotype Portrayed in “I’m a Girl” by Yasmeen Ismail and “Julian is a Mermaid” by Jessica Love Picture Books (EUFONI: Journal of Language, Literary, and Cultural Studies, 2024)
The aim of this thesis is to analyses gender stereotype portrayed and how main character deal with it that is depict in picture books by Yasmeen Ismail and by Jessica Love. The selected picture book entitled I’m A girl and Julian is a mermaid. The books were published in 2015 and 2018. By describing and analyzing the main characters in the picture books, this research uses a qualitative approach. The author used the theory of gender performativity (Butler, 1999) to analyze the data. The study's results demonstrated an analysis of gender stereotype addressing how male and female bodies are distinguished from one another by specific standards of appearance, personal traits, and gender roles that are acceptable in traditional societies for both genders. The finding of analysis I’m A girl picture book shows that how the main character can deal with the gender stereotype by knowing herself and also embracing herself and acts to break gender stereotype. The result of analysis Julian is a mermaid picture book also shows how the male main character breaks the gender stereotype with support by other character. This study concluded that female and male bodies identified as feminine and masculine as they performed certain acts, personal traits, and gender roles' considerations for male and female